UPAYA PERLINDUNGAN HUKUM BAGI KURIR MITRA KERJA DALAM PROSES LAYANAN CASH ON DELIVERY (COD) - Febronia Juniati Sanjaya; Krisnadi Nasution (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
At this moment, business transactions can be done remotely or online, such as through the Grab application. Even though it is done online, payment for business transactions through Grab can be paid in cash when the goods have been received by the buyer, called the Cash On Delivery (COD) service. In business transactions through the Grab application, Grab partners act as couriers to deliver goods from sellers to buyers. The COD system in online transactions has the validity regulated in Pasal 1458 KUHPerdata which states that, "sales and purchases are considered to have occurred between the two parties when the word agree has been reached regarding the goods and prices, even though the goods have not been delivered and the price has not been paid". The transaction creates a legal relationship between two or more legal subjects, and creates rights and obligations that must be met by all parties involved. However, couriers who act as intermediaries between sellers and buyers are often disadvantaged because they do not have protection, either regarding work safety or social security, especially in the COD system. Thus, the purpose of this research is to find out the legal position of couriers in online business transactions and to find out the protection that the courier gets legally when there is a case where the buyer defaults and refuses to pay in the COD system for the goods he ordered online. Based on this, several problems were formulated, such as, “1. What is the legal relationship between Grab couriers and various parties?; and 2. What is the legal protection for Grab couriers in online transactions using the COD system?”. The research conducted by the author uses a method known as normative legal research. This method is carried out by conducting a literature review from secondary data sources, such as laws and regulations, books, and other research in the field of law. In this research, there are several approaches, such as statutory approach, contextual approach, and case approach. The results of this study state that the courier is a substitute party for the company in terms of exercising the authority to deliver goods obtained from the seller, to then be sent to the buyer and then receive payment for the goods that have been sent accompanied by the principle of good faith. Thus, couriers should receive protection from a legal perspective in the form of safety guarantees and social security, especially in the COD system